Value-for-money assessment of social spending in developing countries: lessons from Ethiopia. Issue 8 (17th November 2022) - Harris, Jamelia; Lawson, Andrew
ABSTRACT: This practice note combines key theoretical principles of value-for-money (VfM) assessment with the authors' experiences of conducting these studies in the health and agriculture sectors in Ethiopia. It documents an innovative approach to VfM analysis in contexts where data is limited. The approach combines quantitative and qualitative methods, can be easily applied to policy-relevant questions, and is simple and easily reproducible in developing countries. This practice note is useful to policymakers interested in VfM assessments of social spending in developing countries.